Efektivitas Pelatihan Keterampilan Merajut Dalam Menambahkan Daya Kreativitas Di BLK Singosari - Ferika Nuraniza Yusianto; Imami Arum Tri Rahayu; Ma’rifatun Nashikhah; Peppy Mayasari (Lembaga Pengembangan Kinerja Dosen, 2024)
Job Training Center or often called BLK is a place for training activities to master certain skills so that they can be used as preparation for entering the world of work. Training is one effort to improve the quality of human resources in the world of work. This research aims to determine the effectiveness of knitting skills training activities. This training is also expected to increase the creativity of the training participants in making fashion products or clothing decorations from knitwear that have sales and use value. The methods applied in this training activity are the lecture method and demonstration method on how to knit. The appropriate research method is the questionnaire and observation method. The type of questionnaire used in this research is a closed questionnaire. The data analysis technique from the questionnaire results uses descriptive-qualitative analysis, while the observation results use descriptive analysis. The results of the research cover three main issues, namely: the implementation of knitting training activities that run effectively and according to implementation procedures, the very good impact of knitting training activities for training participants, and the positive response from participants after participating in knitting training activities at BLK Singosari which can be seen from the results of distributing questionnaires and observations during the training activities. The results of distributing the questionnaire showed an increase in the creativity of participants with an average score of 62.5%. Thus, it can be concluded that the effectiveness of this knitting skills training is included in the